The Importance of Security Awareness in Combating Phishing Attacks: A Case Study of Bank Rakyat Indonesia - Dwi Wina Adani; Ida Nurhayati; R. Elly Mirati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The advent of the digital world does not always have positive impacts, it often poses serious attacks that can be highly detrimental to its users, one of which is phishing. Phishing attacks are among the attacks that have been continuously rising in the digital world. With its various forms, phishing stands out as a significant attack, particularly harmful to housewives. Therefore, cultivating security awareness is of paramount importance in preventing customers from becoming victims of phishing attacks. This research aims to explain the importance of security awareness in preventing phishing and to describe the forms of security awareness in combating phishing attacks. The methodology used in this research is quantitative and qualitative methods with simple linear regression analysis, using SPSS 29.0. The sample consists of 80 respondents who are housewives using BRI mobile banking in RT.003, West Tanjung Village, Jagakarsa District, South Jakarta. Primary data collection was conducted through an interview with a BRI informant. The results of the study show that security awareness has a significant impact on reducing phishing attacks. Therefore, enhancing security awareness to prevent phishing is crucial for both individuals and banks to protect information security and avoid becoming victims of digital crimes such as phishing.